Features of Emotional Experiences in Individuals with Personality Disorders - Trzebińska Ewa (Polish Psychological Bulletin, 2014)
Personality disorders (PDs) are marked by significant disturbances in the way of experiencing oneself, others and the world around. Yet there is paucity of research on the nature of emotional experiences in these disorders. The aim of this study was to examine whether and how emotional experience of individuals with ten distinct forms of PDs distinguished in DSM differs from those without PDs. The study was conducted via the Internet on a large nonclinical sample (N = 3509). Participants were administered a PDs measure and a performance task assessing three features of emotional experiences: emotional sensitivity, the valence of experienced emotions and the profile of five components constituting an emotion. As predicted, PDs sufferers experienced emotions differently from controls. Results demonstrated that individuals with all PDs were more receptive to emotional elicitation and displayed higher negative emotionality and a deficiency in the affective component of experienced emotions.